Analysis of free oligosaccharides (fOS) from wild-type Saccharomyces cerevisiae (Baker’s yeast) using two different extraction methods - Iqbal Jalaludin; Amirul Husna Sudin; Dharshini Elangovan; Hussein M. Al-Bajalan; Nur Maisarah Sarizan; Noor Liana Mat Yajit; Kamalrul Azlan Azizan; Abdul Munir Abdul Murad; Farah Diba Abu Bakar; Alonzi, Dominic S.; Mukram Mohamad Mackeen (Penerbit Universiti Kebangsaan Malaysia, 2020)
The glycomic profiles of free oligosaccharides (fOS) derived from misfolded N- and O-linked glycoproteins and lipid-linked oligosaccharides are important molecular signatures in various biological processes and serve as a readout of functional properties such as glycosidase inhibition. Several glycan extraction methods are available based on different sorbent chemistries that may influence the analytical profiles obtained. However, there is limited availability of studies comparing the effects of sorbent chemistries on glycan profiles. Therefore, in our study, the fOS profiles from wild-type Saccharomyces cerevisiae (Baker’s yeast) extracted using two common methods namely mixed-bed ion-exchange (MBIE) [AG50W-X12 (H+) and AG2-X8 (Cl-)] and reversed-phase (C18) sorbents were compared using total carbohydrate (phenol sulfuric acid) and total protein (bicinchoninic acid, BCA) assays, thin-layer chromatography (TLC) and high-performance liquid chromatography-evaporative light scattering detector (HPLC-ELSD) analyses. MBIE extraction contained higher oligosaccharide and protein (0.26 mg/mL and 1.8 mg/mL) content than C18 extraction (0.11 mg/mL and 0.2 mg/mL). TLC analysis (butanol: ethanol: water = 6:3:1 and 5:4:1) showed the presence of fOS in both the MBIE and C18 extracts based on the detection of orcinol active (UV-inactive) spots. Similar peaks were present in the HPLC-ELSD chromatograms for both extractions methods with MBIE showing higher abundance. Glycan unit (GU) analysis of the dextran standard using HPLC-ELSD showed that the largest possible oligosaccharide structures detected were only di/trisaccharides. Based on all these results, MBIE extraction is a more suitable carbohydrate extraction technique compared to C18 extraction for subsequent profiling and functional studies of fOS.